Thyroid hormone resistance: a novel mutation in thyroid hormone receptor beta (THRB) gene - case report - Işık, Emregül; Beck-Peccoz, Paolo; Campi, Irene; Özön, Alev; Alikaşifoğlu, Ayfer; Gönç, Nazlı; Kandemir, Nurgün (The Turkish Journal of Pediatrics, 2013)
Thyroid hormone resistance (THR) is a dominantly inherited syndrome characterized by reduced sensitivity to thyroid hormones. It is usually caused by mutations in the thyroid hormone receptor beta (THRB) gene. In the present report, we describe the clinical and laboratory characteristics and genetic analysis of patients with a novel THRB gene mutation. The index patient had been misdiagnosed as hyperthyroidism and treated with antithyroid drugs since eight days of age. Thyroid hormone results showed that thyrotropin (thyroid-stimulating hormone, TSH) was never suppressed despite elevated thyroid hormone levels, and there was no symptom suggesting hyperthyroidism. A heterozygous mutation at codon 350 located in exon 9 of the THRB gene was detected in all the affected members of the family. It is important to consider thyroid hormone levels in association with TSH levels to prevent inappropriate treatment and the potential complications, such as clinical hypothyroidism or an increase in goiter size.